Resiko Hukum Konsumen Efek Beragun Aset Ditinjau Dari Hukum Perlindungan Konsumen Di Indonesia - Andi Faizkha Haditya; M Yasir; Indra Rahmatullah (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
This research aims to find out any possible risks from an asset backed securities contract, as well as law enforcement carried out by authorities to guaranteed costumer’s protection in the said contract. This research uses qualitative research using regulatory approach. In research data sources come from primary legal materials or field data. The data collection method used in this research are law research and literature studies. The result of this research is there are some possible risks that’s exposed to people involved in this asset backed securities contract as costumer, such as risk of default and early call, which can possibly inflict a financial loss to costumer side, and also finding a loophole that’s still haven’t been taken care off by the regulations regarding this asset backed securities contract. Keywords: Legal Risk, Asset backed securities contract, Costumer’s protection.